2021
DOI: 10.3390/jcm10184050
|View full text |Cite
|
Sign up to set email alerts
|

New Therapies of Liver Diseases: Hepatic Encephalopathy

Abstract: Hepatic encephalopathy (HE) is a common complication of advanced liver disease which has profound implications in terms of the patients’ ability to fulfil their family and social roles, to drive and to provide for themselves. Recurrent and persistent HE is still a serious management challenge, translating into a significant burden for patients and their families, health services and society at large. The past few years have been characterized by significantly more attention towards HE and its implications; its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 80 publications
0
8
0
6
Order By: Relevance
“…Moreover, Et promote the synthesis of endothelin and nitric oxide in HSCs and ECs, which results in increased portal blood pressure [ 40 ]. Because the hemodynamic effects of portal hypertension (PHT) can induce hepatic encephalopathy [ 41 ], HRS [ 42 ], and ascites [ 43 ], it is possible that ADAMTS13:AC and VWF:Ag are associated with these conditions through Et-induced development of hepatic encephalopathy, HRS, ascites, and subsequent PHT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Et promote the synthesis of endothelin and nitric oxide in HSCs and ECs, which results in increased portal blood pressure [ 40 ]. Because the hemodynamic effects of portal hypertension (PHT) can induce hepatic encephalopathy [ 41 ], HRS [ 42 ], and ascites [ 43 ], it is possible that ADAMTS13:AC and VWF:Ag are associated with these conditions through Et-induced development of hepatic encephalopathy, HRS, ascites, and subsequent PHT.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of HE are diverse, manifesting only as reduced attention, memory, or abnormal brain electrophysiology in the early stages of the disease, and as the disease progresses, symptoms of neurological dysfunction such as drowsiness, delirium, or even coma may appear [ 15 ]. Studies [ 16 , 17 ] have shown that HE can cause serious pathological changes related to cerebral edema, gastrointestinal bleeding, renal insufficiency, etc. If patients do not receive timely and effective treatment, it can cause sequelae of multisystem functional disruption and affect their normal life.…”
Section: Discussionmentioning
confidence: 99%
“…This is difficult operatively, as these patients struggle to cope with three main meals and three snacks (frequent hyporexia, dysgeusia, early satiety and prescription of unpalatable diets 104 ), and has not been consistently shown to be beneficial, with the exception of iatrogenic malnutrition deriving from inappropriate or excessively strict dietary prescriptions. 108 A circadian perspective of fasting/feeding patterns may help to explain the difficulties in managing malnutrition in advanced liver disease. Firstly, and as already discussed, the circadian timing system allows to anticipate food intake and the timing of such anticipatory/ preparatory behaviour is not easily modified.…”
Section: Circ Adian Dis Rup Tion In Cirrhos Ismentioning
confidence: 99%
“…Accordingly, malnourished patients with cirrhosis are encouraged to avoid long periods of fasting and to split their food intake into small, frequent meals. This is difficult operatively, as these patients struggle to cope with three main meals and three snacks (frequent hyporexia, dysgeusia, early satiety and prescription of unpalatable diets 104 ), and has not been consistently shown to be beneficial, with the exception of iatrogenic malnutrition deriving from inappropriate or excessively strict dietary prescriptions 108 . A circadian perspective of fasting/feeding patterns may help to explain the difficulties in managing malnutrition in advanced liver disease.…”
Section: Circadian Disruption In Cirrhosismentioning
confidence: 99%